Biological applications of water-soluble polypeptides with ordered secondary structures. Issue 31 (22nd June 2020) - Ge, Chenglong; Ye, Huan; Wu, Fan; Zhu, Junliang; Song, Ziyuan; Liu, Yong; Yin, Lichen
Abstract : Herein, recent advances in the synthesis of the water-soluble polypeptides with ordered secondary structures via ring-opening polymerization of NCA/NTA and their biological applications are described. Abstract : Water-soluble polypeptides are a class of synthetic polymers with peptide bond frameworks imitating natural proteins and have broad prospects in biological applications. The regulation and dynamic transition of the secondary structures of water-soluble polypeptides have a great impact on their physio-chemical properties and biological functions. In this review article, we briefly introduce the current strategies to synthesize polypeptides and modulate their secondary structures. We then discuss the factors affecting the conformational stability/transition of polypeptides and the potential impact of side-chain functionalization on the ordered secondary structures, such as α-helix and β-sheet. We then summarize the biological applications of water-soluble polypeptides such as cell penetration, gene delivery, and antimicrobial treatment, highlighting the important roles of ordered secondary structures therein.